Molecular mechanism and progress in the diagnosis and treatment of familial adenomatous polyposis-associated desmoid tumors - Ge Sai; Wang Xicheng (结直肠肛门外科)
10%-20% of patients with familial adenomatous polyposis complicated with desmoid tumors, which commonly occur in the abdominal cavity or abdominal wall. Although desmoid tumors do not have the ability to metastasize, they can be fatal due to their potential to invade important organs and cause obstruction or ischemia. The activation of the Wnt/β-catenin signaling pathway following APC gene mutation is the cause of this disease. Different APC mutation genotypes are related to the size, growth speed, and severity of desmoid tumors. Targeting Wnt and related pathways is a current research focus in this field. This article reviews the literature to summarize the research on the molecular mechanisms of the disease and the latest advances in diagnosis and treatment.